D is the answer to this question
Answer:
I think 4:1 I'm not that sure tho
Answer:
c. f(x) = (x + 4)(x - 1)
Step-by-step explanation:
Since you're familiar with the product of two binomials:
(x +a)(x +b) = x² + (a+b)x + ab
you know that the constants in the binomial factors must ...
- have a product of -4
- have a sum of +3
__
All of the choices except B have binomial constants that have a product of -4.
In order, the sums of the remaining choices are ...
A: 1-4 = -3
C: 4-1 = 3 . . . . this is the correct choice
D: -2+2 = 0
62.25 + 1 - 1 cause that's just 62.25 + 0 which is 62.25